2002
DOI: 10.4049/jimmunol.168.6.2599
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD83 Regulates the Development of Cellular Immunity

Abstract: We recently found that human CD83, a marker of mature dendritic cells, is an adhesion receptor that binds to resting monocytes and a subset of activated CD8+ T cells. We injected CD83-Ig into mice transplanted with the immunogenic P815 mastocytoma and showed that it significantly enhanced the rate of tumor growth and inhibited the development of cytotoxic T cells. In contrast, mice immunized with CD83-transfected K1735 cells, a poorly immunogenic melanoma, could prevent the outgrowth of wild-type K1735 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
96
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 18 publications
9
96
2
Order By: Relevance
“…Although its exact function is still unknown, various independent studies using soluble forms of CD83 or employing CD83-specific RNA interference provided evidence that this surface molecule is required for efficient DC-mediated T-cell activation [14][15][16][17]19]. Furthermore, it has been shown that CD4 1 single-positive thymocyte development is impaired in CD83 (CD83 À/À ) knockout mice, resulting in pronounced reduction of peripheral CD4 1 T cells [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its exact function is still unknown, various independent studies using soluble forms of CD83 or employing CD83-specific RNA interference provided evidence that this surface molecule is required for efficient DC-mediated T-cell activation [14][15][16][17]19]. Furthermore, it has been shown that CD4 1 single-positive thymocyte development is impaired in CD83 (CD83 À/À ) knockout mice, resulting in pronounced reduction of peripheral CD4 1 T cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a soluble form of CD83 is detectable at low levels in sera derived from healthy individuals, whereas in contrast, elevated levels are present in patients suffering from certain hematological malignancies [8,11]. Notwithstanding the fact that accumulating experimental evidence suggests that CD83 plays an important functional role in the regulation of DCmediated T-cell-specific immune response [12][13][14][15][16][17][18][19], the exact function of CD83 remains poorly understood [20][21][22]. Nevertheless, various disease-related findings suggest that CD83 holds great potential for future therapeutic application [23].…”
Section: Introductionmentioning
confidence: 99%
“…The precise functions of this molecule remain unknown (76,77), but CD83 may serve important roles during intercellular interactions (77)(78)(79), as membrane-bound CD83 increases the stimulatory capacity of DCs (79). Further, previous studies suggest that CD83 mediates adhesion to monocytes and CD8 ϩ T cells (80). CD83-Ig enhances T cell proliferation and increases the proportion of CD8 ϩ T cells (80), and engagement of CD83 delivers a significant signal specifically supporting the expansion, survival and function of newly primed naive CD8 ϩ T cells (81).…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies suggest that CD83 mediates adhesion to monocytes and CD8 ϩ T cells (80). CD83-Ig enhances T cell proliferation and increases the proportion of CD8 ϩ T cells (80), and engagement of CD83 delivers a significant signal specifically supporting the expansion, survival and function of newly primed naive CD8 ϩ T cells (81). CD8 ϩ T cells in lupusprone mice are impaired in expansion, acquisition of memory, secretion of cytokine, and suppression of autoimmunity (8,82) and because CD83 appears to have a role in CD8 ϩ function, it is possible that down-regulation of the former could contribute to abnormal CD8 ϩ function in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the experimental autoimmune encephalomyelitis (EAE) mouse model, injections of sCD83 prevented the disease-associated paralysis under prophylactic as well as therapeutic settings in vivo (21). Scholler and coworkers reported that recombinant expression of a CD83-human Ig and CD83-murine Ig fusion protein inhibited DC-mediated T cell stimulation in vitro in a concentration-dependent manner (22). Additionally, they demonstrated that sCD83 down-modulates antitumor immune responses in vivo using the murine P815 tumor model (22).…”
mentioning
confidence: 99%